Attitude and ad response toward fear appeals in print advertising / Rozlaili Ahmad and Dzulkarnain Mazlan - Ahmad, Rozlaili; Mazlan, Dzulkarnain (Research Management Institute (RMI), 2013)
Fear appeals have been used extensively in marketing communications especially in advertising as a creative strategy format over the course of this century. They are used to threaten or arouse fear in an audience in order to stimulate attitude change. An example of fear appeal advertising that still running now is on how the government addressing some critical issues such as the Anti-Smoking campaign, where represented the damaging effects of smoker's lung, heart and throat. Nevertheless, the increase in various social problems such as drugs, vandalism, crime, healthcare, hygiene has raises the question on the appropriate severity of threat because other types appeals like rational are seen as unable to chance intended behaviour effect. With the increase of technology and power of the media through advertising become more and more instance in which fear appeals are used. Not only fear appeals used to sell products, but they are used to promote health, hygiene and other things. Due to the increase in social issue-related communication, the use of fear as an advertising appeal has raises the question in terms of the fear appeals efficacy in social advertising. Does it work effectively to give an impact towards individual attitude and behavioural change instead of using rational informational appeals which are not having the intended behavioural effect? Does it work towards different group members in our society especially the young generation and how they response to the advertisement? The primarily objectives of the study is to investigate does fear appeals advertising increases the likelihood of adopting appropriate behaviour and the same time to evaluate the attitude towards the elements of fear appeals in advertisement. This research utilized both the quantitative and qualitative methodology. The instruments used to collect the data are using survey method where questionnaire and interview will be distributed and conducted among university students in Kuala Lumpur and Selangor area. The outcome of this research enable for the government bodies and related agencies to plan and employ and effective way to implement an advertising campaign to a specific group of people, create a creative message copy, effective visual images and to make an indigenous media selection targeted to specific audiences for future fear appeals advertisement in print media.